O rei está nu: o discurso da literatura infantil durante a Ditadura Militar no Brasil - Rosa, Daniela Botti da (2014)
In this PhD research, we analyzed the speech of children's literature produced during the period of the military dictatorship in Brazil, following the principles and procedures of discourse analysis of pecheuxs French line. The objective was to understand how the senses of children's literature in this period were produced, verifying the formation of a space within that universe of children's literature, for support of a resistant speech. While in other discursive spaces censorship did become more present, children's literature becomes the stage of metaphorical possibilities for passing directions of resistance to the regime. It is in this speech, a form-heterogeneous subject, which sometimes shows stronger its commitment to the educational process of the child, now seems more open to ways of challenging the existing order.